A assistência social nas ditaduras ibéricas - Pereira, Pedro Teixeira (2022)
Social policy constitutes a half-open door to the ide-ology of the Iberian dictatorial regimes. During the 1930s and 1940s, Salazar and Franco presented themselves to their respec-tive countries as a guarantee of a new political order, articula-ting the discourse around social issues. This article studies how the regimes, through the construction of social assistance, achieved some loyalty of the masses in return, due to their de-pendence on the State and, above all, due to its imposition. However, Salazarism and Francoism reserved a different rele-vance for their welfare policies. A política social constitui-se numa porta entreaberta para ideário dos regimes ditatoriais ibéricos. No decurso dos anos de 1930 e 1940, Salazar e Franco apresentaram-se aos respetivos países como garantia de uma nova ordem política, articulando o discurso em torno das questões sociais. Este artigo estuda como os regimes, através da construção de uma assistência social, conseguiram alguma fidelização das massas em retorno, por dependência perante o Estado e, sobretudo, por imposição do mesmo. Contudo, Salazarismo e Franquismo reservaram diferente relevância para as suas políticas assistencialistas.